Shari‘ah Governance: An Islamic Economic System - Barghouthi, Orobah Ali (International Journal of Shari'ah and Corporate Governance Research, 2018)
This paper examines the roots of shari‘ah in order to provide a solid theoretical foundation that is needed for understanding Islamic jurisprudence in general and Islamic transactional law in particular. Without this minimum understanding of shaiī‘ah, it would be rather difficult to discuss Shari‘ah governance.